PERAN GENDER PADA LEMBAGA KURSUS DAN PELATIHAN DI KOTA TASIKMALAYA - Muhamad Fachri Fasya; Lilis Karwati; Wiwin Herwina (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2022)
Along with the development of the business sector grows rapidly, various community organizations and the educational world seek to increase the role of women in the life of the nation and state. The course and training institutions in Tasikmalaya that worked in the non-formal education sector in this case the course and training institution which the author examined as managers, instructors, and even leaders in the terms of gender roles that women have more roles than men. This study used a qualitative research with descriptive methods, as well as data collection techniques through observation, interviews and documentation. The instrument used through the guidelines of observation, interviews and documentation. The results of this study showed that the role of the gender in the course and training institution that women were very dominant in the management and activities of the course and training institution which showed both in the role of activities, programs, management and in program implementation activities more towards skills for women as well as participants and also students who take part in the implementation of activities in the course and training institution. The fact that many woman worked in the courses and training institutions showed that women can also work not only in domestic spaces, but also in public spaces and the course and training institution as a business that provides a flexible work schedule so that it became a special attraction for women, and the role of women determined by themselves according to their competence.